Peningkatan Kompetensi Guru Bahasa Inggris melalui Pelatihan Pembelajaran Berbasis Proyek yang Kontekstual dan Bermakna: Improving English Teachers Competence through Contextual and Meaningful Project-Based Learning Training - Pramerta, I Gde Putu Agus; Maharani, Anak Agung Putri; Berliani, Ni Wayan Bella; Marini, Kadek Dwi Sapta; Candrawati, Ida Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Project-based learning (PjBL) in elementary and secondary schools is one of the most effective strategies for developing 21st-century skills, including collaboration, creativity, communication, and student responsibility. To strengthen teachers' understanding and competence in implementing project-based learning, especially for English lessons, community service activities (PkM) in the form of education and training should be held. This activity involves English teachers at schools under the Foundation of Perguruan Rakyat Saraswati Pusat Denpasar. The activities provided include lectures on PjBL, training, and guidance on implementing PjBL for PkM participants. The results of the PkM activities show an increase in the knowledge and understanding of English teachers regarding PjBL and how to implement it in a contextual and meaningful manner. Additionally, the survey data indicates a positive response from the teachers toward the PkM activities provided.